Multiple strategies were adopted to optimize the enzymatic characteristics and improve the expression of bovine chymosin BtChy in Kluyveromyces lactis for cheese production - Han, Ying; Zhang, Liu-Qun; Rao, De-Ming; Lei, Lei; Yang, Jiang-Ke (Frontiers in Microbiology, 2025)
Chymosin (EC3.4.23.4), primarily sourced from calf abomasum, serves as a conventional coagulant in milk curdling during cheese production. To improve the enzymatic properties and enhance the expression of calf chymosin (BtChy) in Kluyveromyces lactis to meet the demands of the cheese industry, the in silico engineering via hotspot scanning and molecular dynamics analysis was adopted. This approach improved the activity of BtChy on milk curdling and increased its sensitivity at 65°C. Multiple strategies were utilized to develop an environmentally friendly method for chymosin production. These included screening for constitutive promoters and signal peptides, as well as in vitro construction of a concatemer of the BtChy gene. The optimal combination, comprising the PTDH3 promoter, invertase signal peptide, and a four-copy BtChy gene integrated into the yeast genome, was identified. After high-density cultivation in a 5-L bioreactor, the recombinant yeast achieved an activity of 42,000 SU/mL, a 52.5-fold increase over the original wild-type chymosin gene.